54.5k views
3 votes
When solving the equation, which is the best first step to begin to simplify the equation? Equation: -2 (x + 3) = -10 A: (-2)(-2)(x+3)= -10(-2) B: -1/2(-2)(x+3)= -10(-1/2) C: -2/2(x+3)= -10/2 D: -2/-10(x+3)= -10/-10

2 Answers

4 votes

Answer:

The answer is B

Explanation:

-1/2(2)(x+3)=-10(1/2)

User Slinden
by
5.1k points
0 votes

Answer:

B: -1/2(-2)(x+3)= -10(-1/2)

Explanation:

The best step to begin to simplify the equation is to try to get a coefficient for the variable x equal to 1. we can do that if we multiply in both sides of the equation by -1/2 as option B.

So, if we keep simplifying, we get:

-2 (x + 3) = -10

-1/2(-2)(x+3) = -10(-1/2)

x + 3 = 5

x + 3 - 3 = 5 - 3

x = 2

User Barrett Kuethen
by
5.2k points